Open-heart transcatheter aortic valve replacement in complex aortic valve reoperation: about a case series. Issue 2 (24th May 2018) - Leveille, Laury; Jaussaud, Nicolas; Theron, Alexis; Riberi, Alberto; Collart, Frederic
Abstract: Introduction: Aortic homograft and stentless aortic root are helpful in acute infective endocarditis of the aortic valve as biological conduit when total root replacement is required. Reoperation for failure of aortic homograft and stentless aortic root remains challenging for the surgeon as the entire root can be heavily calcified. Case presentation: Here, are reported, three cases of patients successfully treated with open-heart transcatheter aortic valve replacement (TAVR) whereas no other prosthesis was implantable due to a massively calcified homograft or stentless prosthesis. Discussion: Open-heart TAVR avoided the risk of complete root replacement which is higher than redo aortic valve replacement (AVR). This rescue technique facilitated risky surgical procedure by combining the strengths of both TAVR and conventional AVR.